The scale dependence of the hadron multiplicity in quark and gluon jets and a precise determination of C(A)/C(F) - Abreu, P; Abreu, P; Adam, W; Adye, T; Adzic, P; Ajinenko, I; Albrecht, Z; Alderweireld, T; Alekseev, G; Alemany, R; Allmendinger, T; Allport, P; et al. (1999)
Data collected at the Z resonance using the DELPHI detector at LEP are used to determine the charged hadron multiplicity in gluon and quark jets as a function of a transverse momentum-like scale. The colour factor ratio, CA/CF, is directly observed in the increase of multiplicities with that scale. The smaller than expected multiplicity ratio in gluon to quark jets is understood by differences in the hadronization of the leading quark or gluon. From the dependence of the charged hadron multiplicity on the opening angle in symmetric three-jet events the colour factor ratio is measured to be: CA/CF = 2.246 ± 0.062(stat.) ± 0.080 (syst.) ± 0.095 (theo.) © 1999 Elsevier Science B.V. All rights reserved.